Sex Education Psychoeducation For Parents As An Effort To Prevent Sexual Violence Against Elementary School Students - Khairani, Dini; Aulia, Farah (UNIVERSITAS PAKUAN, 2025)
The increasing cases of sexual violence against children in Indonesia highlight the need for educational interventions to enhance parental knowledge in preventing such incidents. This study aims to evaluate the effectiveness of sex education psychoeducation in improving parents knowledge regarding protecting elementary school students from sexual violence. The method used is a one-group pretest-posttest design, involving 14 mothers as participants. The results showed a significant increase in participants knowledge after the psychoeducation intervention. Thus, sex education psychoeducation is effective as a preventive measure to provide parents with an understanding of the importance of protecting children from sexual violence. This study suggests broader implementation of psychoeducation to build a generation more aware of rights and self-protection